Odpowiedzi

2009-12-20T13:04:16+01:00
A) x²-2½x-6x+15=x²-8½x+15
b)⅜x²-3/16x-x+½=⅜x²-1 3/16x+½
c)⅕x²+3/10x-⅛x-3/16=⅕x²+12/40x-5/40x-3/16=⅕x²+7/40x-3/16
d)⅖x²-4/9x-3/10x+⅓=⅖x²-40/90x-27/90x+⅓=⅖x²-67/90+⅓
Najlepsza Odpowiedź!
2009-12-20T13:32:19+01:00
A)(½ x - 3)(2x - 5)=
=x²-5/2x-6x+15=
=x²-2½x-6x+15=
=x²-8½x+15
b)(¾ x - 2)(½ x - ¼)=
=¾*½x²-¾*¼x-2*½x+2*¼=
=⅜x²-3/16x-x+½=
=⅜x²-1i 3/16x+½
c)(⅖ x - ¼)(½ x + ¾)=
=⅕x²+3/10x-⅛x-3/16=
=⅕x²+12/40x-5/40x-3/16=
=⅕x²+7/40x-3/16
d)(⅔ x - ½)(⅗ x - ⅔)=
=⅖x²-4/9x-3/10x+⅓=
=⅖x²-40/90x-27/90x+⅓=
=⅖x²-67/90+⅓
2009-12-20T13:46:11+01:00
A) (½ x - 3)(2x - 5)=x²-8,5x+15
b) (¾ x - 2)(½ x - ¼)=3/8x²-19/16x+1/2
c) (⅖ x - ¼)(½ x + ¾)=1/5x²+7/40x-3/16
d) (⅔ x - ½)(⅗ x - ⅔)=2/5x²-67/90+1/3